2023
DOI: 10.1128/spectrum.04116-22
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Phenylalanine 23 of Newcastle Disease Virus Matrix Protein Inhibits Virus Release by Disrupting the Interaction between the FPIV L-Domain and Charged Multivesicular Body Protein 4B

Abstract: Multiple viruses utilize a conserved motif, termed the L-domain, to act as a cellular adaptor for recruiting host ESCRT machinery to their budding site. Despite the FPIV type L-domain having been identified in some paramyxoviruses 2 decades ago, its function in virus life cycles and its method of recruiting the ESCRT machinery are poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Previous studies by Li et al 97 confirmed that the binding between NDV M protein and charged multivesicular body protein (CHMP4) promotes virus replication. Similarly, the study by Pei et al 98 demonstrated that the ESCRT-III complex CHMP4s directly interacts with NDV M protein through the FPIV L domain, independently of TSG101, ESCRT-II, or ALIX as assembly factors. In summary, critical amino acid mutations in the FPIV L domain prevent effective interaction between NDV M protein and CHMP4B, resulting in the stalling of viral sub-particles during membrane budding and leading to defects in NDV release and growth.…”
Section: The Role Of Escrt Machinery In Retroviral Buddingmentioning
confidence: 82%
“…Previous studies by Li et al 97 confirmed that the binding between NDV M protein and charged multivesicular body protein (CHMP4) promotes virus replication. Similarly, the study by Pei et al 98 demonstrated that the ESCRT-III complex CHMP4s directly interacts with NDV M protein through the FPIV L domain, independently of TSG101, ESCRT-II, or ALIX as assembly factors. In summary, critical amino acid mutations in the FPIV L domain prevent effective interaction between NDV M protein and CHMP4B, resulting in the stalling of viral sub-particles during membrane budding and leading to defects in NDV release and growth.…”
Section: The Role Of Escrt Machinery In Retroviral Buddingmentioning
confidence: 82%
“…Previous studies by Li et al (2013) confirmed that the binding between NDV M protein and CHMP4 promotes virus replication. Similarly, the study by Pei et al (Pei et al, 2023) demonstrated that the ESCRT-III complex CHMP4s directly interact with NDV M protein through the FPIV L domain, independently of TSG101, ESCRT-II, or ALIX as assembly factors. In summary, critical amino acid mutations in the FPIV L domain prevent effective interaction between NDV M protein and CHMP4B, resulting in the stalling of viral sub-particles during membrane budding and leading to defects in NDV release and growth.…”
Section: The Role Of Escrt Machinery In Paramyxovirus Buddingmentioning
confidence: 89%
“…The newly described sequence motifs PLPPV and FPIV have been shown to also provide late domain activity for viral budding of mouse mammary tumor virus (MMTV) and paramyxoviruses, respectively [ 26 29 ]. Although the ESCRT proteins recruited through the PLPPV motif remain to be identified, the FPIV motif encoded in Newcastle disease virus matrix protein (M protein) appears to facilitate an interaction with CHMP4B [ 30 ]. Nonetheless, it is well established that viral late domain motifs have evolved to mimic the function of proline-rich motifs that facilitate physiological and structural organization of ESCRT components [ 8 ].…”
Section: Overview Of the Host Endosomal Sorting Complex Required For ...mentioning
confidence: 99%